2013
DOI: 10.1080/00343404.2011.624509
|View full text |Cite
|
Sign up to set email alerts
|

Moving across Borders: Who is Willing to Migrate or to Commute?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 31 publications
2
46
0
5
Order By: Relevance
“…Furthermore, it cannot be ruled out that certain respondents may have Huber and Nowotny (2013) showed that the empirical determinants of the willingness to migrate and to commute across the border are in line with outcomes predicted in the previous literature. Studying the determinants of mobility intentions therefore helps reveal the determinants of "real" migration and cross-border commuting decisions, and it can be expected that the factors that determine the individual's willingness to work abroad also affect her decision to work abroad.…”
Section: Willingness To Migrate and Commutesupporting
confidence: 54%
See 3 more Smart Citations
“…Furthermore, it cannot be ruled out that certain respondents may have Huber and Nowotny (2013) showed that the empirical determinants of the willingness to migrate and to commute across the border are in line with outcomes predicted in the previous literature. Studying the determinants of mobility intentions therefore helps reveal the determinants of "real" migration and cross-border commuting decisions, and it can be expected that the factors that determine the individual's willingness to work abroad also affect her decision to work abroad.…”
Section: Willingness To Migrate and Commutesupporting
confidence: 54%
“…In part, this may be due to individuals on maternal/paternal leave, of whom lower mobility intentions can be expected in the short run, or due to discouraged workers who are less willing to seek employment, both in their home countries and abroad. Finally, complementing the results of Huber and Nowotny (2013), a higher level of relative deprivation is associated with an increased propensity to migrate or commute across a border.…”
Section: Empirical Analysismentioning
confidence: 81%
See 2 more Smart Citations
“…This paper therefore analyzes the impact of relative deprivation on the intended duration of stay of potential commuters and migrants. It thus also contributes to research analyzing the willingness to migrate across national borders (see Dalen and Henkens, 2008, for a survey) as well as to the literature on the role of relative deprivation on migration decisions (e.g., Yitzhaki, 1982;Stark and Taylor, 1991;Quinn, 2006) and the contributions analyzing the interaction of migration and commuting choices (e.g., Renkow and Hoover, 2000;Rouwendal and Meijer, 2001;Deding and Filges, 2010;Huber and Nowotny, 2013).…”
Section: Introductionmentioning
confidence: 99%